Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1161/01.atv.21.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein-4 Protease Produced by Smooth Muscle Cells Increases in the Coronary Artery After Angioplasty

Abstract: Abstract-Insulin-like growth factor (IGF)-I stimulates vascular smooth muscle cell (VSMC) migration and proliferation, which are fundamental to neointimal hyperplasia in postangioplasty restenosis. IGF-I action is modulated by several high-affinity IGF binding proteins (IGFBPs). IGFBP-4 is the predominant IGFBP produced by VSMCs and is a potent inhibitor of IGF-I action. However, specific IGFBP-4 proteases can cleave IGFBP-4 and liberate active IGF-I. In this study, we document IGFBP-4 protease produced by hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 48 publications
4
93
0
4
Order By: Relevance
“…These were in agreement with Bayes-Genis et al 7 who observed increased PAPP-A concentrations even in patients with negative cardiac troponin. Pregnancy associated plasma protein-A appeared to be an independent predictor of future ischaemic events as well as the need for percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery.…”
Section: Discussionsupporting
confidence: 92%
“…These were in agreement with Bayes-Genis et al 7 who observed increased PAPP-A concentrations even in patients with negative cardiac troponin. Pregnancy associated plasma protein-A appeared to be an independent predictor of future ischaemic events as well as the need for percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery.…”
Section: Discussionsupporting
confidence: 92%
“…8,9,40,41 In this role, PAPP-A cleaves IGFBP-4 and reduces its affinity for IGFs, effectively increasing local IGF bioavailability. Similar to the observation of increased PAPP-A expression in healing human skin 42 and during vascular repair, 14,15 this could be a mechanism by which PAPP-A induces the proliferation of OSE cells after ovulation and subsequent repair of the ovulation-associated wound.…”
Section: Papp-a In Normal Ovarian Surface Epitheliumsupporting
confidence: 67%
“…12,13 In addition, PAPP-A activation is implicated in injury-repair responses in the vasculature through local increases in bioavailable IGF. 14,15 In spite of its clinical importance, the study of OSE has been limited because of the difficulty in obtaining the cells from rou-tinely handled surgical samples, the small numbers of cells retrieved and the limited lifespan of OSE cells in culture (reviewed in reference 16). To overcome technical limitations, we built upon the work of Dr. N. Auersperg whose laboratory optimized the culture of OSE and transformation by SV40LT, generating IOSE cells.…”
mentioning
confidence: 99%
“…For this protein, which is also found in mammals, specific IGF-independent cleavage of IGFBP-5 identical to PAPP-A and partial activity against IGFBP-3 have been reported (Farr et al, 2000;Bayes-Genis et al, 2001b;Overgaard et al, 2001). These pappalysins contain the sequence motif His-GluXxx-Xxx-His-Xxx-Xxx-Gly-Xxx-Xxx-His/Asp (Xxx for any residue), a zinc-binding consensus sequence (ZBCS) that is the hallmark of the metzincin clan of MPs.…”
Section: Introductionmentioning
confidence: 93%